EFFECTIVENESS OF E-GOVERNMENT IN A TWO-CASE COMPARISON: HEALTH CARE SERVICES IN FINLAND AND ESTONIA - Pöyhönen, Joona (My University, 2014)
This study examines the use of e-government initiatives to make government work more effectively. The study aims to find out the level effectiveness of both the Finnish and Estonian state-level health care sector –specific e-government initiatives, and by comparing the findings, tries to discover differences between the two countries and their e-government initiatives to reveal which factors are the ones making e-government more effective. This study aims to find out how effective health care sector e-government services are right now in both Finland and Estonia and which are the main instruments to improve the level of effectiveness of e-government services in the health care sector. The effectiveness of e-government is researched using the following themes: transparency and accountability, participation and availability and quality and design. The findings are analyzed using a comparative method. The use of comparative method aims to find similarities and differences between the Finnish and Estonian e-government, and also to gain new knowledge on what kind of differences exist, and to find out what kind of effects does these differences have on the outcomes. The analysis revealed that the importance of all themes listed earlier - transparency and accountability, participation and availability and quality and design - has been realized very early on by both countries. Estonian eHealth projects are tied together with the highly touted X-Road architecture. X-Road is aimed for database standardization – so that all different databases of different projects can interact with one another, making it possible to provide the citizen with the best possible e-services. Finnish e-government cannot provide the same flexibility and ability to combine information from different sources as in Estonia. The research shows Estonia being currently ahead of Finland in terms of e-service provision. Estonia has already established some health care e-services that Finland is either just recently implemented or are planning to implement. Statistics show that Estonia is one of the top countries in the world in e-participation. With a high participation level combined with quality health care e-services, Estonia has all the tools needed for an effective e-government.
Keywords: e-government; government effectiveness; health care e-services; fi=Julkisjohtaminen: European Civil Servants - kansainvälisen hallinnon ohjelma|en=Public Management: European Civil Servants|